Method for producing cement clinker using stainless steel slag

By screening and crushing, small-grain powdered steel slag fractions are produced and introduced in the cement kiln, the problems of high chromium content and large energy consumption in cement clinker are solved, and the chromium content is reduced and Energy saving effect.

CN119212960APending Publication Date: 2024-12-27ORBIX PROD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380039500.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-15
Filing Date
2023-04-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, when using stainless steel slag material to produce cement clinker, it is difficult to effectively reduce the chromium content in cement clinker, resulting in the formation of hexavalent chromium and carbon dioxide emissions, and cause additional wear to the raw material mill.

Method used

The solidified stainless steel slag material is used to produce powdered steel slag fractions with particle size less than 0.5mm through screening and crushing, and are introduced in the cement kiln to reduce chromium content and energy requirements while avoiding fine grinding steps.

Benefits of technology

It significantly reduces the chromium content in cement clinker, reduces carbon dioxide emissions and energy consumption, and extends the service life of raw material mills.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005126191200000091
    Figure BDA0005126191200000091
  • Figure BDA0005126191200000101
    Figure BDA0005126191200000101
  • Figure HDA0005126191210000011
    Figure HDA0005126191210000011
Patent Text Reader

Abstract

In a method for manufacturing a cement clinker, a feedstock comprising at least one stainless steel slag is calcined and combusted to produce the cement clinker. The cement clinker can only contain a limited amount of hexavalent chromium, so that the chromium content of the stainless steel slag needs to be limited. This is achieved by solidifying the liquid steel slag such that it comprises a small amount of fine powder sufficient. The fines produced when these fines and / or the coarser fraction of the pulverized steel slag are used to recover stainless steel are used as powdered stainless steel slag for the manufacture of cement clinker. It has been found that these fines have a chromium content that is indeed much less than sand and a coarser coagulation fraction produced from solidified stainless steel slag. The stainless steel slag partially replaces a traditional lime source, carbon dioxide emission can be reduced, and the energy requirement of the cement kiln is lowered. And the powdery stainless steel slag does not need to be finely ground and melted immediately in the rotary kiln.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for manufacturing cement clinker, wherein raw materials including at least one steel slag material are calcined and burned to produce cement clinker. The cement clinker is particularly Portland cement clinker.

[0002] Portland cement clinker comprises lime or calcium oxide (CaO), silicon dioxide (SiO), aluminum oxide (Al2O3) and iron (Fe2O3). It is made starting with raw meal produced from raw materials such as limestone, chalk, shells and shale or limestone as lime source, sand, old bottles and clay or argillaceous rock as silicon source, bauxite, recycled aluminum and clay as alumina source and clay, iron ore, scrap iron and fly ash as iron source. These raw materials are crushed, ground and blended to produce raw meal. In dry process, raw meal is fed to cement kiln in dry state, while in wet process, wet paste is made and fed to cement kiln. In cement kiln, raw materials are heated to calcine carbonate materials and materials are burned to produce cement phase. These cement phases include tricalcium aluminate (Ca3Al2O6 or C3A), tetracalcium aluminoferrite (Ca4Al2Fe2O 10 The cement clinker is a mixture of gypsum, gypsum and alite. The cement clinker is a mixture of gypsum, gypsum and alite. The mixture is then mixed with gypsum and finely ground. Different types of Portland cement can be produced from the cement clinker by adding different cement additives, such as those defined in the 2011 European Standard CEN / EN 197-1.

[0003] The production of cement clinker requires a lot of energy and is a major source of carbon dioxide emissions, not only as a result of fuel combustion, but also as a result of the release of carbon dioxide by the calcination of carbonates contained in the raw materials. In order to reduce energy demand and carbon dioxide emissions, it has been proposed to use steel slag as one of the raw materials. Fresh steel slag produced at high temperatures in steel furnaces does not contain carbonates. Instead of carbonates, they include silicates. Since the calcination reaction of calcium carbonate is highly endothermic, replacing part of the conventional lime source with steel slag can save energy and reduce CO2 emissions from burning fuels. In addition, steel slag does not release carbon dioxide during the calcination step because it contains no or almost no carbonates.

[0004] US2004 / 0157181 discloses the use of coarsely crushed steel slag in the production of Portland cement clinker. The coarse steel slag is not introduced into the kiln at the combustion end, but rather at the feed position in the kiln, thereby increasing the residence time of the steel slag in the kiln. However, due to the large size of the steel slag particles, feeding 10% steel slag in the kiln will result in a large variation in the amount of hydraulic tricalcium silicate and aluminate phases in the cement clinker, and therefore it is necessary to blend the ground clinker to obtain a more uniform composition. Another disadvantage of large steel slag particles is that they cannot be preheated in a preheater or precalciner. The preheater actually includes a cyclone separator through which the finely ground raw meal passes before entering the kiln. The combustion gases leaving the kiln flow upward, countercurrent to the raw meal, and preheat the raw meal through the cyclone separator. The preheater usually includes a zone in which additional fuel is burned to precalcine the calcareous raw material. By feeding the slag material in the kiln at a mid-kiln feed kiln location, the slag particles thus have a lower heating efficiency.

[0005] In the method disclosed in US 6 491 751, granulated steel slag is also used as a raw material for producing cement clinker. However, the crude steel slag is finely ground because it reacts more easily with other elements and compounds contained in the raw material mixture. In addition, due to its high surface area to volume ratio, the finely ground steel slag has a higher thermal reactivity when added to the kiln than the crude steel slag obtained from the steel slag supplier. If the steel slag is finely ground separately from other raw materials in the raw mill, excessive wear or damage to the raw mill may occur. In order to minimize any such possibility, the crude steel slag is first mixed with other raw materials to form a raw meal mixture supplied to the raw mill. The disadvantage of this prior art method is that the steel slag needs to be finely ground, which requires energy, time and additional grinding capacity, and causes additional wear to the raw mill.

[0006] In both prior art methods, the slag supplied as raw material is granulated slag, especially common slag, because the slag is not described as stainless steel slag. In US 6 491 751, the slag is also described as having a relatively high iron content, which indicates that it is a common slag.

[0007] The use of steel slag for the production of cement is also disclosed in CN 107540250 A. This steel slag also contains a large amount of iron, namely 19.41% Fe2O3. It does not contain chromium, so it is obviously not a stainless steel slag. A fine fraction of steel slag with a particle size of less than 0.6 mm is added to the raw meal in an amount of 4 to 6.5 wt.%, and a coarser fraction of steel slag is added to the cement kiln in an amount of 5 to 35 wt.%. Due to its high iron content, steel slag is particularly used to add iron oxide to cement raw materials.

[0008] Compared to stainless steel slag, ordinary steel slag does not contain heavy metals such as chromium and is therefore a less problematic waste material. Ordinary steel slag or fines of finely ground ordinary steel slag can be used, for example, as a soil conditioner, whereas fines of stainless steel slag need to be landfilled under controlled conditions. Since cement can contain only limited amounts of soluble chromium when hydrated, stainless steel slag is not used in practice as a raw material for producing cement clinker.

[0009] However, the use of stainless steel slag for the manufacture of cement clinker is described in EP 0 739 318. The steel slag described in the patent does have an average Cr2O3 content of 1.16 wt.% (equivalent to a Cr content of 7936 mg / kg), while the low free lime content averages only 0.5 wt.%. In order to avoid expensive fine grinding or crushing or grinding steps, the steel slag only needs to be crushed to reduce its particle size to less than 51 mm. The crushed steel slag is introduced into the kiln at the feed end of the kiln and passed through the entire kiln. Steel slag is used to achieve a large amount of energy savings and reduce the emission of volatile substances such as carbon dioxide. The steel slag does melt at a lower temperature, so there is no need to use energy to grind and crush the steel slag. In addition, the steel slag has been heat treated in the steel furnace, so most of the volatile substances have been removed.

[0010] However, as disclosed in EP 1 055 647, coarsely crushed stainless steel slag is a valuable secondary material that can be used to replace natural aggregates in civil or building structures, especially in concrete or asphalt. In such applications, it is found that the chromium contained in the stainless steel slag aggregate is bound and therefore does not cause leaching problems. In addition, due to the low free lime content, the stainless steel slag can be weathered easily to avoid expansion problems. In contrast, ordinary steel slag does not contain chromium, but has a higher free lime content and is therefore less suitable for use in civil construction.

[0011] In the example described in EP 0 739 318, stainless steel slag in amounts of 5 wt.% and 10 wt.% is used in the raw meal for producing cement clinker. Cement clinker in the required amounts of cement phases C3S, C2S, C3A and C4AF can be obtained. The chemical composition of the produced clinker is described in the patent, but the chromium content is not mentioned. However, based on the chromium content of the stainless steel slag, the addition of stainless steel slag can increase the chromium content of the cement clinker by 397 mg / kg for a 5% addition and 794 mg / kg for a 10% addition. Most of the chromium contained in the stainless steel slag is trivalent chromium, which is almost insoluble in water. However, at temperatures between 1400°C and 1500°C, during cement processing in the kiln, chromium III is partially oxidized to chromium VI. The degree of oxidation of chromium varies from kiln to kiln. In practice, for example, about 15% of chromium III can be oxidized to chromium VI in the kiln.

[0012] Hexavalent chromium is known to be carcinogenic, mutagenic and an inducer of dermatitis. According to the EU Directive on chromates (2003 / 53 / EC), cement may not contain more than 2 ppm of soluble chromium (VI) when hydrated. According to the STN EN 196-10 standard - "Methods of testing cement" - Part 10: "Determination of the water-soluble chromium (VI) content of cement". In the assessment of the safety of ferrous sulfate with regard to its mutagenic potential and reproductive toxicity, the opinion of the Scientific Advisory Committee to Examine the Toxicity and Ecotoxicity of Chemical Compounds (CSTE / 93 / 12 / COM) has described a correlation between the water-soluble chromium VI content in cement and skin allergic reactions.

[0013] Ferrous sulfate is the most commonly used reducing agent in cement. In practice, the reduction of chromium VI in cement can be achieved by adding 0.35 wt.% of ferrous sulfate to cement. Once the cement is wetted, ferrous sulfate reduces the water-soluble chromium VI to the less soluble chromium III. According to Christina Laskowski in her article "Iron (II)-sulfate as concrete admixture for chromium (VI) reduction", the maximum recommended dosage of ferrous sulfate heptahydrate (FeSO4.7H2O) is 0.5 wt.%. By adding this amount of ferrous sulfate to cement containing 21.8 ppm chromium VI, the amount of soluble chromium VI is reduced to less than 0.1 ppm during hydration. In addition, although the cement properties are affected by ferrous sulfate, the requirements for cement admixtures are also met. The addition of 0.5 wt.% ferrous sulfate delays the initial setting time of slag cement and Portland cement, but accelerates the initial setting of high-strength cement grades. Final setting was retarded for all cement types tested except CEM I 52,5R Portland cement.

[0014] The object of the present invention is to provide a novel method for manufacturing cement clinker, in which stainless steel slag can be used as one of the raw materials, which method allows the chromium content of the cement clinker to be reduced for an equal amount of stainless steel slag supplied to the cement kiln, without having to use a larger amount of reducing agent.

[0015] For this purpose, the method according to the invention is characterized in that it comprises the following steps:

[0016] - providing a stainless steel slag comprising trivalent chromium and a non-metallic slag phase, the stainless steel slag having been solidified from liquid stainless steel slag to produce a solidified stainless steel slag, the solidified stainless steel slag comprising slag particles having a sieve size of less than 0.5 mm in an amount of less than 70 wt.%, preferably less than 60 wt.%, more preferably less than 50 wt.% and most preferably less than 40 wt.%, based on the non-metallic slag phase, and the non-metallic slag phase of the solidified stainless steel slag consists for at least 40 wt.% of crystalline non-metallic slag phases;

[0017] - separating a powdered slag fraction from the solidified stainless steel slag and / or from the granular material, the powdered slag having a D of less than 0.5 mm 90 The particle size distribution of the sieve size value, the pellets have a D value greater than 5.0 mm, preferably greater than 6.0 mm and more preferably greater than 8.0 mm. 90a first particle size distribution of sieve size values ​​and produced by reducing the particle size of solidified stainless steel slag; and

[0018] - Using the powdered steel slag fraction as the steel slag material for producing the cement clinker.

[0019] According to the present invention, it has been found that the powdered slag fraction of solidified stainless steel slag or coarsely crushed solidified stainless steel slag contains considerably less chromium than the coarse sand and aggregate fractions of solidified stainless steel slag. When the solidified stainless steel slag is completely crushed and finely ground into a powdered material, this powder has a certain total chromium content, which is equal to the average chromium content of stainless steel slag. However, according to the present invention, the powdered slag fraction should be separated from the stainless steel slag during solidification and / or after the particle size of the solidified stainless steel slag has been reduced, for example by crushing, in order to produce a material that is still sufficiently coarse and in particular has a D of more than 5.0 mm. 90 By separating the powdered slag fraction from the stainless steel slag as it solidifies and / or from the coarsely crushed stainless steel slag, the powdered slag fraction has a much lower chromium content than the remaining coarser fraction or fractions of the stainless steel slag. Furthermore, this powdered stainless steel slag fraction already has a small particle size and therefore does not need to be finely ground to be used as a raw material to be fed into a cement kiln.

[0020] When solidifying the stainless steel slag, the solidified slag should be cooled sufficiently quickly in order to avoid complete dusting of the slag, otherwise the fine stainless steel slag fraction will not have a reduced chromium content. The solidified stainless steel slag should contain less than 70 wt.% of slag particles smaller than 0.5 mm, i.e. passing through a sieve with 0.5×0.5 mm openings. This weight percentage should be determined based on the weight of the non-metallic slag phase, i.e. excluding any steel contained in the stainless steel slag material. Preferably, the solidified stainless steel slag should contain an even smaller amount of such small stainless steel slag particles, i.e. less than 60 wt.%, preferably less than 50 wt.% and more preferably less than 40 wt.% based on the weight of the non-metallic slag phase in the stainless steel slag and in the small particles.

[0021] Furthermore, the liquid slag must be solidified in such a way that the non-metallic slag phase comprises at least 40 wt.% of a crystalline non-metallic slag phase. Thus, the liquid slag may not be solidified by quenching or granulation (with water), as this would result in a predominantly amorphous slag. Although this has not yet been confirmed, the formation of a crystalline phase is believed to be key to achieving the difference in chromium content between the powdered slag fraction and the coarser slag fraction.

[0022] One or more coarser fractions of the solidified stainless steel slag can be used as fine (sand) or coarse aggregates for the production of concrete or asphalt, preventing the chromium contained in the stainless steel slag aggregates from leaching in the concrete or asphalt. The powdered steel slag fraction has a low chromium content and can therefore be used in large quantities as a raw material for the manufacture of cement clinker in order to limit carbon dioxide emissions and the energy requirements of the clinker manufacturing process. Preferably, the raw material for the manufacture of cement clinker comprises at least 1wt.% and more preferably at least 2wt.% of the steel slag material. Due to the small particle size of the powdered stainless steel slag fraction, it can be fed at any desired position in the rotary kiln, particularly at the hot end or the feed position in the kiln. In the case of a wet process, the powdered slag is preferably fed to the rotary kiln at one or more of these positions, otherwise the powdered slag will absorb considerable water from the wet paste. For dry process kilns with preheaters, it can also be fed at the feed position in the kiln or at the hot end or at the feed end in a rotary kiln, but it is preferably mixed with the raw meal or fed to the preheater together with the other parts of the raw meal so that the powdered slag is also preheated by the gases leaving the kiln.

[0023] In an embodiment of the method according to the invention, it comprises the step of reducing the particle size of the solidified stainless steel slag to produce said granular material, and the step of separating at least part of said powdered slag fraction from said granular material. Preferably, said part of said powdered slag fraction is separated from said granular material before carbonization of the non-metallic slag phase contained in said part of said powdered slag fraction occurs, or before the non-metallic slag phase contained in said part of said powdered slag fraction takes up up to 3.0 wt.%, preferably up to 2 wt.% and more preferably up to 1 wt.% of carbon dioxide by carbonizing the non-metallic slag phase.

[0024] The advantage of this embodiment is that the granules from which the powdered slag fraction has been removed are valuable aggregate materials for concrete or asphalt. In addition, by reducing the particle size of the solidified stainless steel slag, more valuable stainless steel can be recovered therefrom. At the same time, more powdered slag fractions are released, which can be used in the method of the present invention as a raw material for producing cement clinker. The non-metallic slag phase contained in the granules from which the powdered slag fraction is removed is preferably uncarbonized or only a small amount of carbonized. This means that, by the carbonization of the non-metallic slag phase, the non-metallic slag phase contained in the part separated from the granular material in the powdered slag material can absorb up to 3.0wt.%, preferably up to 2.0wt.% and more preferably up to 1.0wt.% of carbon dioxide. The uptake of carbon dioxide can occur before and / or after reducing the particle size of the solidified stainless steel slag material to produce granules. The uptake of carbon dioxide can be by reacting with the carbon dioxide contained in the atmosphere, that is, by natural weathering / aging. Before separating the powdered stainless steel slag fraction from the granular material, carbonization is preferably avoided or limited because, due to carbonization, the fine slag particles can agglomerate to form larger particles, so that the fine slag particles with a lower chromium content can no longer be effectively separated from the coarser slag particles with a higher chromium content.

[0025] Slag particles with a sieve size of less than 0.5 mm can remain in the solidified stainless steel slag used in the particle size reduction step to produce the granules. In this way, they do not need to be processed separately from the fine particles produced when reducing the particle size of the solidified stainless steel slag. This embodiment is particularly advantageous in the case where the solidified stainless steel slag contains only a limited amount of fine particles, for example less than 50 wt.% or less than 40 wt.%.

[0026] Alternatively, part of the powdered slag fraction can be separated from the solidified stainless steel slag before reducing its particle size to produce the granular material. In this case, the part of the powdered slag fraction is separated from the solidified stainless steel slag before any carbonization of the non-metallic slag phase contained in the part of the powdered slag fraction occurs, or before the non-metallic slag phase contained in another part of the powdered slag fraction takes up up to 3.0 wt.%, preferably up to 2 wt.% and more preferably up to 1 wt.% of carbon dioxide by carbonizing the non-metallic slag phase. Furthermore, in this case, before separating the powdered stainless steel slag fraction from the solidified stainless steel slag, carbonization is preferably avoided or limited, because due to carbonization, fine slag particles can agglomerate to form larger particles, so that fine slag particles with a lower chromium content can no longer be effectively separated from coarser slag particles with a higher chromium content. The embodiment in which part of the powdered slag fraction has been separated from the solidified stainless steel slag is particularly advantageous in the case where the solidified stainless steel slag contains a relatively large amount of fine particles, for example more than 50 wt.% or more than 60 wt.%. It is already possible to remove the solidified stainless steel slag before it is further crushed and subjected to screening and steel recovery operations. Thus, more material can be processed with the same device. Furthermore, the powdered stainless steel slag fraction recovered in this way can be separated from the dried stainless steel slag, and therefore no further drying is required before it is introduced into the cement clinker plant or the cement clinker plant itself.

[0027] In an embodiment according to the method of the present invention or according to any one of the preceding embodiments, the particle size of the solidified stainless steel slag is reduced by crushing the solidified stainless steel slag to produce the granules having the first particle size distribution. The granules can be produced in particular by a crushing and screening operation, wherein the oversized particles are re-crushed.

[0028] The term pulverization means squeezing or beating into small pieces. By pulverizing stainless steel slag, the particle size (size of the particles) is reduced by splitting, while by grinding the steel slag, its particles are reduced to powder by friction. Compared with the grinding operation, the pulverization operation applies less friction to the particles, so less fine powder is produced in the pulverization operation due to friction. The fine powder produced by the pulverization operation is more the result of the disintegration (disintegration) of the weaker parts of the stainless steel slag particles. It has been found that, like the fine powder of the solidified stainless steel slag itself, these weaker parts contain less chromium than the stronger and larger stainless steel particles. The weaker parts can be due to the fact that the transformation of β-dicalcium silicate to γ-dicalcium silicate is partially disintegrated, resulting in the expansion of the dicalcium silicate phase, and the slag falls or dusts, making the slag unable to be used as an aggregate. The inventors have found that the falling fraction of the slag contains much less chromium than the strong aggregate fraction of the stainless steel slag, and therefore, can be used in large quantities in the production of cement clinker. Part of the fallen dust fraction in the stainless steel slag is already present in the stainless steel slag in solidified form, but another part is produced or released when the particle size of the solidified stainless steel slag is reduced, in particular by pulverizing it. Before separating the powdered slag fraction from the pellets, part of the powdered slag fraction may have been separated from the solidified stainless steel slag, and another part from the pulverized stainless steel slag or the solidified stainless steel slag can first be pulverized to produce the pellets, which pellets include fines already present in the solidified stainless steel slag. Both parts of the powdered slag fraction are preferably uncarbonized or contain at most 3.0 wt.%, preferably at most 2.0 wt.% and more preferably at most 1.0 wt.% of carbon dioxide in the form of carbonates, based on their non-metallic slag phases. The amount of carbon dioxide can be determined by TGA analysis, wherein the powdered slag fraction is first heated to 110°C to remove any water and determine the dry weight, and wherein the powdered slag fraction is further heated to 550°C to remove hydroxides and then to 950°C to decompose carbonates and remove the generated carbon dioxide. The carbon dioxide uptake percentage is the amount of carbon dioxide divided by the dry weight of the slag fraction, multiplied by one hundred. Preferably, the particle size of the solidified stainless steel slag is reduced by pulverizing the solidified stainless steel slag in at least two consecutive steps to produce the granules, a coarser granules being produced by a first pulverizing step, and a portion of the granules being removed from the coarser granules before the coarser granules are subjected to a second pulverizing step to produce another portion of the granules.

[0029] An advantage of this preferred embodiment is that less fines are produced, particularly less fine particles having a higher chromium content, and less aggregate (sand) of lower value compared to coarser aggregates.

[0030] Preferably, after the first comminution step, a first stainless steel-rich fraction is separated from the coarser particulate material before removing said portion of said particulate material from said coarser particulate material.

[0031] Stainless steel is a valuable material that can be reused in the stainless steel production process, especially in the EAF (Electric Arc Furnace).

[0032] In an embodiment according to the method of the invention or according to any of the preceding embodiments, the granules are separated by sieving into at least two different fractions, including granules having a D of less than 4 mm, preferably less than 3 mm or more preferably less than 2 mm. 90 A fine fraction of the sieve size value, and a coarser fraction coarser than the fine fraction, from which at least part of the powdered slag fraction is separated. The coarser fraction may contain more than 5000 mg / kg, in particular more than 5500 mg / kg and more in particular more than 6000 mg / kg of chromium.

[0033] The fine fraction includes a relatively large amount of powdered slag fraction. When the sand fraction is separated from the fine fraction, the powdered slag fraction still exists.

[0034] Preferably, a second stainless steel-rich fraction is separated from said coarser fraction.

[0035] Since the particles contained in the coarser fraction are more uniform in size, it is possible to recover additional stainless steel from the coarser fraction, particularly by gravity separation techniques such as by a jig.

[0036] At least part of the fine fraction is preferably mixed with water to produce an aqueous mixture, the aqueous mixture is separated in a sand fraction and an aqueous dispersion, in particular by a dewatering classifier such as a dewatering screw, and at least part of the powdered slag fraction is extracted from the aqueous dispersion, in particular filtered out of the aqueous dispersion. At least part of the powdered slag fraction is preferably filtered out of the aqueous dispersion, leaving a filtrate that is stored in at least one reservoir, in which a precipitate containing stainless steel slag particles is produced, and at least part of the precipitate is taken out of the reservoir to produce another part of the powdered slag fraction.

[0037] The third stainless steel rich fraction is preferably pulverized by a ball mill, stainless steel is recovered from the pulverized third stainless steel rich fraction, and the remaining pulverized slag is recycled into the aqueous mixture before the aqueous mixture is separated in the sand fraction and the third stainless steel rich fraction is separated from the aqueous mixture in the aqueous dispersion, preferably by gravity separation techniques.

[0038] Since the particles contained in the fine fraction are more uniform in size, it is possible to recover additional stainless steel from the fine fraction, in particular by gravity separation techniques, such as by a hydrosizer. Due to the smaller size of the particles in the stainless steel-rich fraction, there is still a greater amount of slag adhering to the stainless steel particles. In this embodiment, the stainless steel particles are cleaned by subjecting them to a comminution operation, preferably by means of a ball mill.

[0039] In an embodiment according to the method of the invention or according to any of the preceding embodiments, the non-metallic slag phase of the powdered slag fraction contains less than 5000 mg / kg, preferably less than 4500 mg / kg and more preferably less than 4000 mg / kg of chromium. Since the powdered slag fraction is separated from stainless steel slag, it contains chromium, in particular more than 1000 mg / kg of chromium.

[0040] The lower chromium content enables the use of larger amounts of powdered stainless steel slag as a raw material for making cement clinker without having to add more reducing agents to the cement, or enables the addition of less reducing agents (such as ferrous sulfate) to the cement to reduce its hexavalent chromium content.

[0041] In an embodiment according to the method of the invention or according to any of the preceding embodiments, the non-metallic slag phase of the solidified stainless steel slag comprises more than 5000 mg / kg, preferably more than 5500 mg / kg and more preferably more than 6000 mg / kg of chromium.

[0042] Thus, solidified stainless steel slag is a secondary material produced when making stainless steel, particularly stainless steel containing at least 10.0 wt. % chromium.

[0043] In an embodiment according to the method of the invention or according to any of the preceding embodiments, the powdered slag fraction comprises a crystalline non-metallic slag phase comprising at least 3 wt.%, preferably at least 5 wt.% and more preferably at least 7 wt.% of γ-dicalcium silicate (γ-C2S or calico-olivine).

[0044] In the method according to the invention, the powdered slag fraction is not a finely ground fraction, but is separated from solidified stainless steel slag and / or from relatively coarse-grained stainless steel slag obtained by reducing the particle size of solidified stainless steel slag. It therefore comprises a large number of particles which result from the disintegration of the slag due to the transformation of β-C2S into γ-C2S. The γ-C2S content of the powdered material is therefore higher than in the coarser fractions of the slag. The mineralogy and basicity of the powdered material are therefore different from those of the remaining coarser part of the stainless steel slag, which may be a possible explanation for the lower chromium content of the powdered material.

[0045] The present invention also relates to a method for producing cement clinker, wherein raw materials including at least one steel slag material are calcined and burned to produce cement clinker, and wherein the powdered steel slag fraction obtained as described above is used as the steel slag material.

[0046] Since the powdered stainless steel slag fraction is obtained by the process steps defined above, it has a reduced chromium content compared to one or more other stainless steel slag fractions. Therefore, a larger amount of this powdered stainless steel slag fraction can be used in order to limit carbon dioxide emissions and energy requirements of the clinker manufacturing process.

[0047] The powdered stainless steel slag fraction can be used in a newly produced state, but can also be stored first, for example in a pile outdoors. During storage, it can be carbonized to a certain extent by natural carbonization. Only a limited amount of carbonates are formed in this way, so there is only a limited impact on the carbon dioxide emissions of the cement kiln. By carbonizing the powdered stainless steel slag fraction, its particles can be agglomerated. However, in the cement kiln, they will soon fall and spread apart during the calcining step. The agglomerated stainless steel slag fraction can also be ground, which will not cause great wear on the raw material mill, because the particles or clumps of the agglomerated stainless steel slag fraction are not difficult to grind. If the stainless steel slag fraction is to be added to the paste of the wet cement kiln, it can be carbonized, preferably after granulation into larger particles, to reduce its water uptake. In this way, the addition of the carbonized powdered stainless steel slag fraction will not increase the water demand of the wet paste, or will not increase it to a lesser extent.

[0048] Preferably, the steel slag is a stainless steel slag, the non-metallic slag phase of which contains less than 5000 mg / kg, preferably less than 4500 mg / kg and more preferably less than 4000 mg / kg of chromium, and the stainless steel slag comprises a crystalline non-metallic slag phase, which comprises at least 3 wt.%, preferably at least 5 wt.% and more preferably at least 7 wt.% of gamma-dicalcium silicate.

[0049] The invention also relates to the use of the powdered steel slag fraction obtained as defined above as a raw material for the manufacture of cement clinker.

[0050] Other advantages and particularities of the present invention will become apparent through the following description of some specific embodiments of the method for manufacturing cement clinker according to the present invention. This description is given as an example only and is not intended to limit the scope of the present invention. The reference numerals used in the description relate to the accompanying drawings, in which:

[0051] Figure 1 It is a schematic diagram of an in-line calcining kiln;

[0052] Figure 2A and Figure 2B Two parts of a flow chart of a particular embodiment of a method for producing a powdered stainless steel slag fraction which can be used for manufacturing cement clinker according to the method of the invention.

[0053] In the present specification and claims, unless otherwise stated, % or wt. % refers to dry weight percentage.

[0054] The expression "slag phase" refers to a non-metallic slag phase, which may be amorphous or crystalline. Therefore, the expression "slag phase" does not encompass a steel phase or steel particles. Such steel particles may be embedded in the non-metallic slag phase or may consist of individual steel particles, which may be coated or covered with the slag phase.

[0055] The chromium content is expressed in mg Cr / kg dry weight, in particular in mg / kg dry weight of the non-metallic slag phase, unless it is explicitly stated that it is related to the amount of Cr2O3. Therefore, the metallic phase / particles are first removed from the slag. The amount of chromium is determined by ICP after complete destruction of the non-metallic slag phase with an acid mixture of HNO3, HCl and HBF4, as described in the guidelines CMA / 2 / II / A.3 and CMA / 2 / I / B.1 for the sampling and analysis of waste and soil samples (both published in the BelgianOfficial Gazette / Moniteur belge on January 11, 2021). ICP analysis is in particular ICP-OES analysis.

[0056] The present invention relates to a method for producing cement clinker, in particular Portland cement clinker. After the cement clinker is produced and cooled, a certain amount of gypsum (CaSO4.2H2O or ) is added to the cement clinker and the mixture is finely ground. The cement clinker thus obtained generally comprises 25-50 wt.% C3S, 20-45 wt.% C2S, 5-12 wt.% C3A, 6-12 wt.% C4AF and 2-10 wt.% The cement clinker mixed with gypsum contains preferably less than 5 wt.% MgO.

[0057] After the raw materials are mined, crushed, ground and homogenized, the first step in cement production is the calcination of calcium carbonate, and the resulting calcium oxide then reacts with silicon dioxide, aluminum oxide and ferrous oxide at high temperatures to form clinker. The clinker is then polished or ground with gypsum and other ingredients to produce cement. Naturally formed calcareous deposits (such as limestone, marl or chalk) provide a source of calcium carbonate. Silicon dioxide, iron oxide and aluminum oxide are present in various ores and minerals. Several types of waste can also serve as partial substitutes for natural raw materials.

[0058] The cement industry is energy intensive, with energy typically accounting for about 40% of production costs. A variety of conventional fossil fuels and waste fuels can be used to provide the heat energy requirements required for the process. Basically, the characteristics of the clinker combustion process itself allow waste to be used as raw materials and / or fuels. Clinker combustion is carried out in a rotary kiln, which can be part of a wet or dry long kiln system, a semi-wet or semi-dry grate preheater (Lepol) kiln system, a dry suspension preheater kiln system or a preheater / precalciner kiln system.

[0059] In the method according to the present invention, at least one powdered stainless steel slag is used as one of the raw materials for manufacturing cement clinker. In practice, ordinary steel slag (such as LD slag) has been used for the production of cement clinker. However, the disadvantage of LD slag is that its free lime content is relatively high. The free lime in the LD slag is completely burned, so it is not easy to dissolve or melt in the kiln, and therefore it can not react in the cement clinker. The free lime in the cement clinker must be closely monitored to ensure the quality of cement. Too much free lime does lead to adverse effects such as volume expansion, increased setting time or reduced strength. LD slag also requires fine grinding, which increases the grinding cost because the slag contains silicates that are high in hardness and difficult to grind.

[0060] Compared with ordinary steel slag, stainless steel slag has a lower free lime content. Stainless steel slag is produced in a furnace for producing stainless steel (i.e., steel comprising iron and at least chromium, in particular at least 10wt.% chromium). Typically, it also includes nickel and / or molybdenum. Specifically, stainless steel slag is produced in an EAF (Electric Arc Furnace), an AOD (Argon Oxygen Decarburization) furnace, a VOD (Vacuum Oxygen Decarburization) furnace, a ladle (ladle, ladle slag) or a tundish (tundish, for continuous casting of molten steel). Due to its high heavy metal content, stainless steel slag fines are more problematic waste materials because ordinary steel slag fines can, for example, be used as soil conditioners. They also cannot be used in asphalt or concrete because they have high water absorption. Therefore, it is necessary to find new applications in which stainless steel slag fines can be used as secondary raw materials.

[0061] In the method according to the invention, powdered stainless steel slag material is used as secondary raw material for making cement clinker. Cement clinker is preferably produced in a dry process rotary kiln, because dry process kilns require less energy and therefore also produce less carbon dioxide compared to wet or semi-wet process kilns. The kiln is preferably equipped with a preheater, wherein the raw meal is heated by heat recovered from the kiln or the clinker cooling section. The preheater may be a preheater / precalciner when part of the fuel is burned in the preheater / precalciner.

[0062] In practice, there are different types of cement clinker plants, including pre-calciner units, i.e., In-Line Calciner (ILC) and Separate Line Calciner (SLC). More specifically, the kiln can be a so-called preheater kiln, an air-through calciner, an in-line calciner, an in-line calciner with a combustion chamber and an air-separated calciner. Such installations are well known to those skilled in the art, so the in-line calciner will be described below only as an example.

[0063] like Figure 1As shown, the in-line calciner comprises a plurality of cyclones, in this case five cyclones 1 to 5 connected by four risers 6 to 9 and a precalciner unit 10 which together form a heat exchange cyclone tower 11. An updraft is generated in the cyclone tower 11 by a draft fan (ID fan) in a discharge pipe 12. Raw clinkermeal is usually introduced into the riser 6 between the second cyclone 2 and the first cyclone 1. After passing through the cyclone tower 11, the heated and at least partially calcined (decarbonized) raw clinkermeal is directed to the feed end 14 of the rotary drum kiln 15 via the kiln feed pipe 13. Due to having passed through the precalciner unit 10, where a temperature of 870-900° C. is generated, the degree of calcination of the material introduced into the rotary drum kiln 15 is between 90% and 95%. The material is then conveyed through the kiln 15 by a combination of the kiln inclination and its rotational movement. As shown by arrow 19, a burner is provided at the end of the rotary drum kiln 15, which produces a flame through which air is supplied in the kiln. When the material approaches the flame, the material temperature rises and clinkerisation occurs. When leaving the kiln, the material is discharged to the grate cooler 16, where it exchanges heat with secondary air and is thereby cooled to produce cement clinker.

[0064] In order to heat the precalciner unit 10 and generate an ascending air flow therein, the combustion gas (i.e., kiln gas having a temperature of about 1000° C.) generated by combustion in the rotary kiln 15 is guided to the bottom of the precalciner unit 10 through the kiln ascending duct 17. In addition, the tertiary air heated to about 750-900° C. in the grate cooler 16 is also guided to the precalciner unit 10 by the tertiary air duct 18. These tertiary air enter the precalciner unit 10 along a tangent line to generate a moderate swirl to ensure effective mixing of the fuel, raw meal and gas. The temperature in the precalciner unit 10 is further controlled by the burner supplied with fuel and primary air. Therefore, the air for burning the fuel in the precalciner unit is composed of kiln gas, tertiary air from the cooler and fuel conveying / atomizing air provided by the precalciner burner in the precalciner unit, as shown by arrow 20. About 55% to 60% of the fuel is supplied to the precalciner burner, while the remaining fuel is supplied to the kiln burner.

[0065] The powdered stainless steel slag fraction used in the method according to the invention can be added to the raw meal and can therefore also be fed to the heat exchange cyclone tower 11 via the riser 6. On the other hand, since it contains no carbonates or only a small amount of carbonates, calcination is not required and therefore it can also be fed directly to the rotary kiln 15 via its feed end 14.

[0066] In the case of a wet kiln, the raw meal is fed into the rotary kiln in the form of a wet paste at the feed end. The powdered stainless steel slag fraction can also be introduced into the rotary kiln at this feed end. Preferably, since the powdered stainless steel slag fraction used in the method according to the invention has a relatively high water absorption, it will increase the amount of water required to produce the wet paste, so it is not added to the wet paste. In the case of a wet kiln, the powdered stainless steel slag fraction is preferably introduced into the kiln at a kiln feed position in the kiln, which is located in the calcination zone. A burner is provided at this position, via which additional fuel is introduced into the kiln. The powdered stainless steel slag fraction is melted quickly at this position because it has a relatively low melting temperature. Therefore, it can be prevented from leaving the kiln via the outflow of the combustion gases from the kiln. As an alternative or in addition, the powdered stainless steel slag fraction can also be introduced at the combustion end of the rotary kiln, but the stainless steel slag will have less time to react and mix with the other constituent elements of the cement clinker.

[0067] In the method according to the invention, the powdered stainless steel slag fraction used as raw material for the manufacture of cement clinker is produced in such a way that it has a lower chromium content than the steel slag from which it is produced and in such a way that no additional fine grinding step is required. The powdered stainless steel slag fraction is produced starting from air-cooled stainless steel slag which, apart from any stainless steel particles contained therein, comprises a crystalline slag phase and generally also an amorphous slag phase, the crystalline slag phase comprising a chromium-containing phase. The powdered stainless steel slag fraction is not obtained by fine grinding of solidified stainless steel slag, but rather by grinding it to give it a D 90 The particles with a sieve size value less than 0.5 mm are separated from the particle size distribution.

[0068] D 90 The sieve size value is the particle size at which 90% of the volume cumulatively passes. According to ASTM D6913 / D6913M-17, the particle size distribution can be tested using a sieve with square openings. The volume percentage of the particles can be calculated in particular by dividing the weight of the particles passing through the sieve by the average density of the material forming the particles.

[0069] Air-cooled stainless steel slag is produced by pouring liquid stainless steel slag into a slag field and allowing it to solidify. The cooling of the solidified stainless steel slag is preferably accelerated, in particular by spraying water on the solidified slag. Compared with the granulation method, this air-cooling method results in a slower solidification rate of the liquid steel slag. In this way, the solidified steel slag is not completely amorphous, but includes a crystalline slag phase and a common but not necessary amorphous slag phase. The non-metallic phase of the solidified stainless steel slag should include at least 40wt.%, preferably at least 50wt.% of a crystalline non-metallic slag phase (i.e., a mineral phase). They may also include an amorphous non-metallic slag phase, especially at least 20wt.% of an amorphous non-metallic slag phase, more specifically at least 25wt.% of an amorphous non-metallic slag phase.

[0070] Part of the powdered stainless steel material used to make cement clinker can be separated from the solidified stainless steel slag. The solidified stainless steel slag does already contain such an amount of particles, the sieve size of which is less than 0.5 mm. Preferably, after these smaller particles or parts of the particles have been removed from the solidified stainless steel slag or after these smaller particles have not been removed from the solidified stainless steel slag, the particle size of the solidified stainless steel slag is reduced to produce a granular material with a first particle size distribution, the first particle size distribution having a D value that should still be greater than 5.0 mm. 90 Screen size value.

[0071] The cooling of the slag should be controlled in such a way that the amount of particles with a sieve size of less than 0.5 mm (i.e. the amount of fines) calculated on the non-metallic slag phase should be less than 70 wt.%, preferably less than 60 wt.%, more preferably less than 50 wt.% and most preferably less than 40 wt.%. The amount of non-metallic slag phase contained in these slag fines should be less than 70 wt.% of the total amount of non-metallic slag phase, i.e. 70 wt.% of the total amount of solidified slag. This amount depends not only on the slag chemistry but also, in particular, on the way the liquid slag is cooled. For example, the technology disclosed in EP 3 122 909 can be used to keep the amount of fines below these maximum values.

[0072] A preferred embodiment of a method for producing a powdered slag fraction of stainless steel slag, which can be used to make cement clinker and has a reduced chromium content, is shown in Figure 2. Liquid stainless steel slag from different ladles and furnaces in a stainless steel production plant is poured into a cooling pond in a slag field, where the liquid slag is air-cooled, that is, allowed to slowly solidify and cool. During the cooling process, water can be sprayed on the solidified slag to accelerate the cooling process to a certain extent, especially at its end. Due to the relatively slow solidification rate, the slag does not solidify almost completely in the amorphous phase, but solidifies to a large extent in the form of a crystalline phase. One of the mineral phases of stainless steel slag is dicalcium silicate (C2S). When the crystalline dicalcium silicate cools, it undergoes several polymorphs:

[0073] α has a hexagonal crystal structure.

[0074] αH' has an orthorhombic crystal structure.

[0075] αL' with orthorhombic crystal structure,

[0076] β having a monoclinic crystal structure, and

[0077] γ with an orthorhombic crystal structure.

[0078] In the case of pure dicalcium silicate under laboratory conditions, the αL'-dicalcium silicate undergoes a transformation to β-dicalcium silicate at 675°C, followed by a transformation from β-dicalcium silicate to γ-dicalcium silicate at 490°C. Due to the transformation of β-dicalcium silicate to γ-dicalcium silicate, the volume increases by 12% due to its different crystal structure, which will destroy the dicalcium silicate phase. This will crush a fraction of the slag and produce fine powder. This transformation also causes micro cracks in the powdery particles, which seems to explain why the fine powders produced thereby are able to absorb and retain large amounts of water. These water absorption properties make these fine powders very unsuitable for most uses in construction. However, according to the present invention, it has been found that these fine powders are suitable for use as raw materials for making cement clinker. Their chromium content is indeed lower than that of the coarser fractions in stainless steel slag, and they already have a small particle size and therefore do not need to be finely ground. In order to limit the generation of fines during the cooling process, the cooling can be accelerated, in particular by spraying water onto the solidifying slag, so that the slag cools faster, in particular from temperatures above 500° C., and less β-dicalcium silicate can be converted into γ-dicalcium silicate.

[0079] In the process shown in Figure 2, solidified stainless steel slag 31 is stored in a slag bin 32. The slag 31 is fed to a hopper 33, which includes a grid for stopping all oversized slag pieces 34, which in this particular case are slag pieces larger than 300 mm. Since the oversized pieces can damage the crusher used in the subsequent process, these oversized pieces 34 are removed for special treatment later, such as crushing with a hammer and extracting large metal fragments before being fed again through the hopper 33.

[0080] Slag particles 35 smaller than 300 mm fall onto the conveyor belt through the hopper 34 and are transported to the first metal manual sorting cabin 36, where an operator removes large metal chunks 37 from the slag particles 35 on the conveyor belt. Figure 2AIn a next step, not shown in the figure, the slag particles 35 can be screened to remove fine powder or parts thereof having a particle size of less than 0.5 mm or less. These fine powders are dry or relatively dry, and therefore do not need to be dried before feeding them to the cement clinker plant. The slag particles 35 or the remaining slag particles are crushed in the first crusher 38 to produce crushed slag 39, which is conveyed along the first metal separation tape 40, and metal particles 41 are removed from the crushed slag particles 39 to reach the first screen 42. The slag particles 39 then pass through the first screen 42, which separates them into three fractions: particles 43 greater than 35 mm, particles 44 between 10 mm and 35 mm, and particles 45 less than 10 mm. The fraction of particles 43 greater than 35 mm is taken away by the second conveyor belt through the second metal sorting cabin 46, where more metal pieces 47 are removed. The particles 43 greater than 35 mm are then put back into the first crusher 38. The fraction of particles 44 between 10 mm and 35 mm enters a second crusher 48 to produce further crushed slag 49, which is fed to a second screen 50. The further crushed slag 49 is separated into three fractions in the second screen 50: a fraction 51 of particles larger than 20 mm, a fraction 52 of particles smaller than 10 mm, and a fraction 53 of particles between 10 mm and 20 mm. The fraction 53 of larger particles between 10 mm and 20 mm is passed by a third conveyor belt through a second metal separation tape 54, where more metal 55 is removed and returned to the second crusher 48. The fraction 51 of particles larger than 20 mm passes through a third metal separation tape 56, where more metal 57 is removed and stored in a box 58. This fraction 51 is a valuable coarse aggregate for construction and road construction. The fraction 45 of particles smaller than 10 mm from the first sieve 42 and the fraction 52 of particles smaller than 10 mm from the second sieve 50 are combined together to form 0-10 mm pellets 59 which are stored in a bin 60 .

[0081] like Figure 2B As shown, the granular slag material 59 is supplied to a third screen 61 which is a 2 mm screen that separates the particles of the 0-10 mm stainless steel slag granular material 59 into a fine fraction 62 of less than 2 mm and a coarser fraction 63 between 2 mm and 10 mm.

[0082] The coarser fraction 63 is fed to a wet screening device or screening machine, where metal particles 65 are removed from the coarser 2-10 mm fraction 63. The screening machine 64 is preferably a linear pressure screening machine, as described by Andrew Falconer in "Gravity Separation: Old Techniques / New Methods" in Physical Separation in Science and Engineering, 2003, Vol. 12, No. 1, pp. 31-48. The screening machine 64 is filled with water, wherein the stainless steel slag particles are subjected to a jigging action, so that the heavier metal particles 65 are separated from the lighter slag particles 66 by gravity. The lighter slag fraction 66 passes through a fourth metal separation tape 67, where a metal-rich fraction 68 is removed, and the slag fraction 66 is stored in a box 69. This fraction 66 is a valuable fine aggregate for construction and road construction. The metal-rich fraction 68 is finely ground to recover the metal particles contained therein. The remaining finely ground demetallized fraction is a filler fraction which can be used as filler, for example in concrete or asphalt.

[0083] The third screen 61 is preferably a wet screen to which water is supplied. Thus, the fine fraction 62 is mixed with water to produce an aqueous mixture 70. This aqueous mixture is also produced with water 71 from a screening machine 64 containing fine slag material washed off from the coarser slag fraction 63.

[0084] The aqueous mixture 70 is fed to a hydraulic classifier 72. The working principle of the hydraulic classifier 72 is also described in the article "Gravity Separation: Old Techniques / New Methods" by Andrew Falconer. In the hydraulic classifier 72, a stainless steel-rich fraction 73 is separated from the aqueous mixture 70. This stainless steel-rich fraction 73 is fed to a first gravity separation screw 74, the overflow 75 from the first gravity separation screw 74 is added again to the aqueous mixture 70, and the underflow 76 is fed to a ball mill 77, where slag adhering to the stainless steel particles is removed therefrom. The crushed material 78 leaving the ball mill crusher 77 is fed to a second gravity separation screw 79. The overflow 80 of this second gravity separation screw 79 is added again to the aqueous mixture 70, and the underflow is a valuable fine stainless steel fraction 81.

[0085] The aqueous mixture 70 comprising the slag fractions 75 and 80 removed from the stainless steel-rich fraction 73 is fed to a dewatering classifier, in particular a dewatering screw 82, wherein, as an underflow, a sand fraction 83, in particular a sand fraction of 0.5-2 mm, is removed from the aqueous mixture 70. This sand fraction 83 can be used as a fine aggregate for the production of concrete or asphalt. The overflow leaving the dewatering screw 82 is an aqueous dispersion 84 of fine slag particles in water.

[0086] In order to remove fine slag particles from the aqueous dispersion 84, the aqueous dispersion 84 is fed to a hydrocyclone 85. The working principle of the hydroclassifier 72 is described in the article "Gravity Separation: Old Techniques / New Methods" by Andrew Falconer. The underflow 86 of the hydrocyclone 85 is filtered through a disc filter 87 to remove fine slag particles that form a powdered slag fraction 88. The overflow 89 of the hydrocyclone 85 is further processed in a thickener 90, and the overflow 91 of the thickener 90 is pumped into a reservoir 92, while the underflow 93 is processed with the disc filter 87. Therefore, other fine slag particles removed by the thickener 90 also reach the powdered slag fraction 88. The filtrate 94 leaving the disc filter 87 is also supplied to the reservoir 92.

[0087] The purified water contained in the reservoir 92 can be reused to supply water to the wet screen 61 and the screening machine 64. In the reservoir 92, other fine stainless steel slag materials will settle to the bottom to produce a precipitate 95. This precipitate can be removed from the reservoir 92 from time to time and can be added to the powdered stainless steel slag fraction 88.

[0088] Experimental data

[0089] The following experimental data are shown, with reference Figure 2A and 2B The powdered stainless steel slag fraction 88 produced by the method is suitable for use as a raw material for producing cement clinker.

[0090] Average particle size

[0091] First, the average particle size distribution of a large number of samples of the powdered stainless steel slag fraction 88 produced by the disc filter 87 was measured. The results are shown in Table 1.

[0092] Table 1: As reference Figure 2A and 2B As described, the average particle size distribution as well as the minimum and maximum particle size distributions of 240 samples of the powdered stainless steel slag fraction produced by the disc filter 87 are shown.

[0093]

[0094] Based on the average particle size distribution of these samples, D 90 The sieve size value is equal to about 0.18 mm, while for the smallest sample size (largest pass), D 90 The sieve size value is equal to about 0.125 mm, and for the sample with the largest particle size (smallest passing), D 90 The sieve size value is equal to about 0.4 mm. The powdered slag fraction 88 is therefore composed of smaller particles and, therefore, does not require any further fine grinding for melting in the cement kiln. Moreover, the particle size is so small that, in the case of a dry process, it can even be added directly to the raw meal fed to the preheater / precalciner.

[0095] Chemical composition

[0096] As an example, a sample of the powdered stainless steel slag fraction 88 produced by the disc filter 87 and a sample of the precipitate 95 taken from the reservoir 92 have been analyzed by ICP after complete destruction with a mixture of acids, in particular with a combination of HNO3, HCl and HBF4. The following results were obtained:

[0097] Table 2: Elemental analysis of a sample of the powdered stainless steel slag fraction 88 from the disc filter 87 and of a sample of the precipitate produced in the reservoir 92, expressed in mg of element / kg dry weight and as wt. % oxides.

[0098]

[0099] In addition, the powdered slag fraction produced by the disc filter also contains: <120Br, 17200F, 220Cl, <200K, 2560Na, 6090Ti, 15Cu, 245Ni, 17Zn, 215Ba, 9.8Co, 8980Mn, 60.2Mo, 11.2Se, 152V, 1860S and 1380B, in mg / kg dry weight. In addition, the precipitate also contains <110Br, 15000F, 310Cl, 370K, 4440Na, 5010Ti, 15Cu, 161Ni, 26Zn, 236Ba, 7.3Co, 5820Mn, 38.4Mo, <10.0Se, 119V and 1710S.

[0100] It can be seen that the calcium and silicon content of these two materials are very high, and the calcium-silicon ratio is similar to that in cement clinker. Aluminum is also an essential element in cement clinker. Chromium is unwelcome, and the amount of soluble chromium after cement hydration produced from cement clinker must be kept below 2ppm. This can be achieved by limiting the amount of powdered stainless steel slag fraction used as a raw material for producing cement clinker, and by adding a sufficient amount of reducing agent in cement. Non-limiting examples of suitable reducing agents include ferrous sulfate (FeSO4), particularly ferrous sulfate heptahydrate (FeSO.7H2O), stannous chloride (SnCl2), stannous sulfate (SnSO4), stannous oxide (SnO), stannous hydroxide (Sn(OH)2), manganous sulfate, iron sulfide (FeS) and / or ferrous chloride (FeCl2), particularly ferrous chloride tetrahydrate (FeCl2.4H2O) and combinations thereof. Preferred reducing agents are FeSO4.7H2O, SnSO4, SnCl2, SnO, SnO(OH)2 and combinations thereof.

[0101] When not stored / aged, the powdered slag fraction collected by the disc filter and piled together contains only limited amounts of carbonates. The carbonate content of this fresh powdered slag fraction was measured by TGA over a period of one year. On average, the fresh powdered slag fraction contained 1.6 wt.% CO2, with a maximum of 2.5 wt.% and a minimum of 0.4 wt.%. These carbonates are formed during the processing of the stainless steel slag, but some of them are formed after the powdered slag fraction is separated from the granular slag material. The precipitate collected from the reservoir was found to contain more carbonates. The water used in the device is indeed highly alkaline after contact with the stainless steel slag particles, and will therefore easily absorb carbon dioxide from the atmosphere. It was found that this carbon dioxide was precipitated in the form of fine calcium carbonate particles and was therefore contained in the precipitate 95 collected from the reservoir 92 in addition to the stainless steel slag particles. For some samples, the release of CO2 was measured by TGA analysis. These amounts vary between 3 wt.% and 7 wt.% CO2, corresponding to calcium carbonate contents varying between about 7 wt.% and about 16 wt.%. Only about 4 wt.% to 9 wt.% of CaO is bound in these carbonates, so that most of the CaO is still contained in other compounds, such as silicates, which do not release CO2 when used to make cement clinker.

[0102] The maximum amount in which these powdered slag fractions can be used as raw materials for producing cement clinker is limited by the MgO content. In cement clinker, the MgO content should indeed be less than 5 wt.%. However, the maximum amount will still be about 30 wt.%. At such an amount, other parameters of cement clinker (such as Na2O eq , Cl, SO3 and DOS (degree of sulfation)) are not restricted. The only limiting parameter will be the chromium content.

[0103] Reduce chromium content

[0104] In the past ten years, the above reference Figure 2A and 2B The method described produces a powdered stainless steel slag fraction 88. However, during this time, the precipitate 95 formed in the reservoir is not collected and therefore not added to the powdered steel slag fraction 88.

[0105] Liquid stainless steel slag used to produce solidified stainless steel slag is sourced from the EAF and AOD of the stainless steel plant. The liquid slag is slowly solidified and then cooled more quickly by spraying water on the solidified slag. In this way, the production of fines in the slag pit is limited. These fines are also removed by Figure 2A and Figure 2B The solidified stainless steel slag 31 is treated by the method shown, and thus reaches a powdered stainless steel slag fraction 88. On average, the powdered stainless steel slag fraction 88 accounts for about 30% of the total amount of the coarse aggregate and finer aggregate fractions 51 and 66, the sand fraction 83, and the powdered stainless steel slag fraction 88. The amount of fine powder generated in the slag pit was not measured, but can be estimated to be about 70% of the amount of the powdered stainless steel slag fraction 88, i.e., to about 20% of the total amount of the non-metallic slag phase contained in the solidified stainless steel slag 31.

[0106] The steel slag fractions are stored in boxes in piles. The 2-10 mm fraction 66 is divided into two fractions, namely, a 2-6 mm aggregate fraction and a 6-10 mm aggregate fraction. Table 3 gives the results of different analyses of the chromium content in the different fractions produced during a ten-year period. The analyses were carried out in different production years, shortly after the production of the different slag fractions. Thus, the results cover the production of stainless steel slags over a ten-year period. During these years, different types of stainless steel were produced in the steel plant. In addition, the slag was produced in different furnaces, in particular in EAF and AOD furnaces.

[0107] Table 3: Use the above reference Figure 2A and Figure 2B Chromium content in mg Cr / kg dry weight in different powder, sand and aggregate fractions produced by the described process over a period of ten years.

[0108] 0-0.5mm 0.5-2mm 2-6mm 6-10mm 1 3600 4800 5700 4600 2 1600 3300 3200 5279 3 3900 8360 4140 7930 4 3603 8788 6068 7408 5 3910 5520 5660 4780 6 3620 6920 10400 7880 7 3040 7130 5650 8730 8 3100 6210 11200 7360 9 2850 5800 8230 6080 10 2550 6900 4010 4310 average value 3177 6373 6426 6436

[0109] According to these analysis results, the average chromium content of the fine (sand) and coarse aggregate fractions of stainless steel slag is almost the same, while the average chromium content of the powdered (0-0.5 mm) fraction is much smaller, that is, the chromium content is only about half of the chromium content of the aggregate fraction. Since the chromium content in stainless steel slag seems to be a factor limiting stainless steel slag as a raw material for producing cement clinker, the use of the powdered stainless steel slag fraction instead of the aggregate fraction enables the use of about twice the amount of stainless steel slag. In addition, the powdered stainless steel slag fraction melts faster in the cement kiln, does not require fine grinding, and is suitable for feeding to the preheater / precalciner.

[0110] Some stainless steel slag fractions collected over the years have been analyzed by XRD to analyze their crystalline phase. On average, the different stainless steel slag fractions contain about 35 wt.% amorphous slag phase and about 65 wt.% crystalline phase. Although some powdered stainless steel slag fractions have a higher amorphous phase content and less chromium content, this does not explain why the powdered slag fractions have a much lower chromium content.

[0111] However, the XRD results show that the content of olivine (γ-dicalcium silicate) varies greatly. The γ-C2S content of the powdered stainless steel slag fraction varies between 6.2% and 16.5% of the crystal slag phase, with an average of 11.3%. For the aggregate fraction, the γ-C2S content varies between 1.6% and 3.4% of the crystal slag phase, with an average of 2.6%. Although chromium does not accumulate in dicalcium silicate, the γ-C2S content can be an indication of the basicity of the slag. In fact, the higher the basicity of the slag, the greater the tendency to form γ-C2S. Generally, chromium exists in stainless steel slag as spinel phases, that is, as MgO (Al2O3, Fe2O3, Cr2O3) phases. When the basicity of the slag is low, these spinel phases may contain more chromium. This may be one of the reasons why the chromium content of the powdered stainless steel slag fraction is much lower than that of the aggregate fraction.

[0112] XRD determination of magnesiochromite content

[0113] Magnesia-chrome spinel is a spinel phase with a higher chromium content. Most of the chromium in stainless steel slag is contained in this magnesia-chrome spinel phase. The magnesia-chrome spinel content of freshly produced powdered steel slag fraction 88 was analyzed approximately twice a week over a period of one year. A total of 120 samples were analyzed. The average content of the magnesia-chrome spinel phase was equal to 3.21% of the crystallized slag phase, with a minimum equal to 1.1% and a maximum equal to 5.4%.

[0114] Eight demetallized filler fractions obtained by finely grinding and demetallizing the metal-rich fraction 68 were analyzed by XRD. The average content of the magnesia-chrome spinel phase of these samples was equal to 10.00% of the crystalline slag phase, the minimum was equal to 9.2% and the maximum was equal to 12.1%. Thus, the magnesia-chrome spinel content of this finely ground and demetallized 2-10 mm slag fraction was more than 3 times higher than that of the powdered steel slag fraction 88.

[0115] In terms of the γ-C2S content, the γ-C2S content of the powdered stainless steel slag fraction 88 is also much higher than that of the demetallized filler fraction, namely, 8.01% on average, while the filler fraction is 1.17%.

[0116] Predicted chromium (VI) content of cement clinker composition

[0117] The powdered stainless steel slag fraction contains no or substantially no hexavalent chromium (i.e., Cr(VI)). However, during the high temperature slaking process, part of the Cr(III) present in the powdered stainless steel slag fraction is converted to Cr(VI). The degree of oxidation depends on the cement kiln and the calcination / slaking process. It depends, for example, on the gases present in the kiln, in particular its oxygen content.

[0118] In the article "Removal of soluble Cr(VI)in Cements by Ferrous Sulfate Monohydrate, solid lignin and other Materials" by Emin Erdem et al., Ceramisc Slikaty, March 2011, three different cement types were tested, i.e., CEM I 42.5R, containing 190.4 mg / kg of total chromium; CEM I / AP 42.5N, containing 125.2 mg / kg of total chromium; and CEM IV / B(P)32.5N, containing 56.3 mg / kg of total chromium. Total chromium includes Cr(III) and Cr(VI). Soluble chromium (i.e., Cr(VI)) measured according to STN EN 196-10 standard should be less than 2 ppm. The soluble chromium contents of these three cements are 17 ppm, 11 ppm and 4.5 ppm respectively. To reduce the soluble chromium content to 2 ppm, 0.16 wt.%, 0.08 wt.% and 0.04 wt.% of ferrous sulfate heptahydrate were added, respectively. These amounts are substantially proportional to the total chromium content in the cement.

[0119] Adding 5 wt% of a powdered stainless steel slag fraction with a total chromium content of 3000 ppm will increase the Cr content of the cement by about 150 ppm. Thus, the Cr content of CEM I 42.5R cement will almost double, and therefore the soluble chromium content and the amount of reducing agent required will also almost double. It can therefore be estimated that a total amount of about 0.30 wt% of ferrous sulfate heptahydrate determined according to STN EN 196-10 will be sufficient to keep the soluble Cr(VI) content below 2 ppm. This amount is well below the maximum recommended dosage of 0.5 wt.% mentioned by Christina Laskowski in the publication mentioned above.

[0120] It can be calculated that by replacing 5% of the calcium carbonate in the raw clinker with the powdered stainless steel slag fraction, a reduction of about 6% to 7.5% in CO2 emissions caused by calcination can be achieved, depending on the composition of the raw meal. In addition, about 5% of energy can be saved and CO2 emissions from fuel can be additionally reduced.

[0121] It is also possible to obtain a higher amount of powdered stainless steel slag by adding a higher amount of reducing agent or, for example, by selecting a source of stainless steel slag. For example, some types of stainless steel contain only about 12% chromium, while other types of stainless steel contain 17% to 18% chromium, and therefore, the slag floating on the top of the molten stainless steel will also contain less chromium. It is also possible to reduce the chromium content in the stainless steel slag, for example, by adding metallic aluminum to the liquid slag floating on the liquid steel, which will chemically reduce the chromium and reduce the chromium content of the slag. As described in EP 3 901 289, adding aluminum in a stainless steel furnace can also reduce the formation of fine powder in the solidified steel slag. In addition, the higher aluminum content in the powdered stainless steel fraction increases the value of this fraction as a raw material for cement clinker production, because cement clinker must also contain aluminum oxide.

Claims

1. A method for producing cement clinker, wherein: The raw materials including at least one steel slag material are calcined and burned to produce the cement clinker, the method comprising the following steps: - providing a stainless steel slag (31) comprising trivalent chromium and a non-metallic slag phase, the stainless steel slag (31) having been solidified from liquid stainless steel slag to produce a solidified stainless steel slag (31), the solidified stainless steel slag comprising slag particles having a sieve size of less than 0.5 mm in an amount of less than 70 wt.% based on the non-metallic slag phase, and the non-metallic slag phase of the solidified stainless steel slag comprising at least 40 wt.% of a crystalline non-metallic slag phase; - separating a powdered slag fraction (88) from the solidified stainless steel slag (31) and / or from the granular material (59), the powdered slag fraction having a D 90 The particle size distribution of the sieve size value, the pellets have a D greater than 5.0 mm 90 a first particle size distribution of sieve size values, and the granules are produced by reducing the particle size of solidified stainless steel slag (31); and - Using the powdered steel slag fraction (88) as the steel slag material for producing the cement clinker.

2. The method according to claim 1, characterized in that The method comprises the steps of reducing the particle size of solidified stainless steel slag (31) to produce the granular material (59), and separating at least part of the powdered slag fraction (88) from the granular material (59).

3. The method according to claim 2, characterized in that The portion of the powdered steel slag fraction (88) is separated from the pellets (59) before any carbonization of the non-metallic slag phase contained in the portion of the powdered steel slag fraction (88) occurs, or before the non-metallic slag phase contained in the portion of the powdered steel slag fraction (88) takes up up to 3.0 wt.%, preferably up to 2 wt.% and more preferably up to 1 wt.% of carbon dioxide by carbonizing the non-metallic slag phase.

4. The method according to claim 2 or 3, characterized in that: The slag particles having a sieve size of less than 0.5 mm are retained in the solidified stainless steel slag (31), which is used in the particle size reduction step to produce the granules (59).

5. The method according to claim 2 or 3, characterized in that: Before reducing the particle size of the solidified stainless steel slag to produce the granular material (59), in particular before any carbonization of the non-metallic slag phase contained in another part of the powdered steel slag fraction occurs, or before the non-metallic slag phase contained in another part of the powdered steel slag fraction takes up up to 3.0 wt.%, preferably up to 2 wt.% and more preferably up to 1 wt.% of carbon dioxide by carbonizing the non-metallic slag phase, the other part of the powdered steel slag fraction is separated from the solidified stainless steel slag (31).

6. The method according to any one of claims 2 to 5, characterized in that The solidified stainless steel slag (31) is crushed to reduce the particle size of the solidified stainless steel slag (31) to produce the granular material (59) having the first particle size distribution.

7. The method according to claim 6, characterized in that The granules (59) are produced by reducing the particle size of the solidified stainless steel slag (31) by comminuting the solidified stainless steel slag (31) in at least two consecutive steps, producing coarser granules (39) by the first comminuting step, and removing a portion (45) of the granules (59) from the coarser granules (39) before subjecting the coarser granules (39) to a second comminuting step to produce another portion (52) of the granules (59).

8. The method according to claim 7, characterized in that After the first comminution step, a first stainless steel-rich fraction (41) is separated from the coarser granular material (39) before removing the portion (45) of the granular material (59) from the coarser granular material (39).

9. The method according to any one of claims 2 to 8, characterized in that The pellets (59) are separated into at least two different fractions (62, 63) by sieving, wherein the at least two different fractions include a particle size having a D of less than 4 mm. 90 A fine fraction (62) of a sieve size value and a coarser fraction (63) coarser than the fine fraction (62), at least a portion of the powdered slag fraction (88) is separated from the fine fraction (62).

10. The method according to claim 8 or 9, characterized in that: A second stainless steel-rich fraction (65) is separated from the coarser fraction (63).

11. The method according to any one of claims 8 to 10, characterized in that At least part of the fine fraction (62) is mixed with water to produce an aqueous mixture (70), the aqueous mixture (70) is separated into a sand fraction (83) and an aqueous dispersion (84), in particular by means of a dewatering classifier (82), and at least part of the powdered slag fraction (88) is extracted from the aqueous dispersion (84).

12. The method according to claim 11, characterized in that Prior to separating the aqueous mixture (70) from the sand fraction (83) and the aqueous dispersion (84), a third stainless steel-rich fraction (73) is separated from the aqueous mixture (70) by a gravity separation technique, the third stainless steel-rich fraction (73) is preferably pulverized by means of a ball mill (77), stainless steel (81) is recovered from the pulverized third stainless steel-rich fraction (79), and the remaining pulverized slag (80) is recycled to the aqueous mixture (70).

13. The method according to claim 11 or 12, characterized in that: At least part of the powdered steel slag fraction (88) is filtered out of the aqueous dispersion (84) to leave a filtrate (94), which is stored in at least one reservoir (92), in which a precipitate (95) containing stainless steel slag particles is produced, and at least part of the precipitate (95) is removed from the reservoir (92) to produce another part of the powdered steel slag fraction (88).

14. The method according to any one of claims 1 to 13, characterized in that The non-metallic slag phase of the powdered steel slag fraction (88) contains less than 5000 mg / kg, preferably less than 4500 mg / kg and more preferably less than 4000 mg / kg of chromium.

15. The method according to any one of claims 1 to 14, characterized in that The non-metallic slag phase of the solidified stainless steel slag (31) comprises more than 5000 mg / kg, particularly more than 5500 mg / kg and more particularly more than 6000 mg / kg of chromium.

16. The method according to any one of claims 1 to 15, characterized in that The powdered slag fraction (88) comprises a crystalline non-metallic slag phase comprising at least 3 wt.%, preferably at least 5 wt.%, and more preferably at least 7 wt.% of gamma-dicalcium silicate.

17. The method according to any one of claims 1 to 16, characterized in that The raw material comprises at least 1 wt.%, preferably at least 2 wt.% of the steel slag material.

18. The method according to any one of claims 1 to 17, characterized in that At least the portion of the powdered steel slag fraction is separated from the solidified stainless steel slag (31) before the non-metallic slag phase contained in the portion of the powdered steel slag fraction is carbonized, or before the non-metallic slag phase contained in the portion of the powdered steel slag fraction takes up at most 3.0 wt.%, preferably at most 2 wt.% and more preferably at most 1 wt.% of carbon dioxide by carbonizing the non-metallic slag phase.

19. A method for producing cement clinker, wherein: Raw materials comprising at least one steel slag material are calcined and burned to produce cement clinker, and wherein a powdered steel slag fraction (88) which has been obtained as defined in any one of claims 1 to 18 is used as the steel slag material.

20. Use of a powdered steel slag fraction that has been obtained as defined in any one of claims 1 to 18 as raw material for the manufacture of cement clinker.

21. The method according to claim 19 or the use according to claim 20, wherein The steel slag is a stainless steel slag, which contains less than 5000 mg / kg, preferably less than 4500 mg / kg and more preferably less than 4000 mg / kg of chromium, and the stainless steel slag includes a crystalline non-metallic slag phase, which includes at least 3 wt.%, preferably at least 5 wt.% and more preferably at least 7 wt.% of gamma-dicalcium silicate.